(3GdMRH GdcHjQs - (3GdTGPdj, CHh GdMSf, fhQ GdOjf, Ydj Hf YHO Gddg Hf YHO GdLHGQ, J(B656(3g`s
(3ChdgG (B:s
(3QHfG Ydjc JhcdfG hEdjc CfHfG hEdjc GdeUjQ ZaQGfc QHfG hEdjc GdeUjQ QHfG GZaQ dfG PfhHfGs
(3BNQgG (B:s
(3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 305s
(3eYLe GdeDdajf(B: 2 / 467s
(3cTa GdXfhf(B: 1 / 662s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs